Redundant and Non-redundant Functions of the AHK Cytokinin Receptors During Gynoecium Development - Cerbantez-Bueno, Vincent E.; Zúñiga-Mayo, Victor M.; Reyes-Olalde, J. Irepan; Lozano-Sotomayor, Paulina; Herrera-Ubaldo, Humberto; Marsch-Martinez, Nayelli; de Folter, Stefan (Frontiers in Plant Science, 2020)
The phytohormone cytokinin is crucial for plant growth and development. The site of action of cytokinin in the plant is dependent on the expression of the cytokinin receptors. In Arabidopsis, there are three cytokinin receptors that present some overlap in expression pattern. Functional studies demonstrated that the receptors play highly redundant roles but also have specialized functions. Here, we focus on gynoecium development, which is the female reproductive part of the plant. Cytokinin signaling has been demonstrated to be important for reproductive development, positively affecting seed yield and fruit production. Most of these developmental processes are regulated by cytokinin during early gynoecium development. While some information is available, there is a gap in knowledge on cytokinin function and especially on the cytokinin receptors during early gynoecium development. Therefore, we studied the expression patterns and the role of the cytokinin receptors during gynoecium development. We found that the three receptors are expressed in the gynoecium and that they have redundant and specialized functions.